Forging communities : food and representation in medieval and early modern Southwestern Europe - Piera, Montserrat (Food and foodways (Fayetteville, Ark.), 2018)
Forging Communitiesexplores the importance of the cultivation, provision, trade, and exchange of foods and beverages to mankind's technological advancement, violent conquest, and maritime exploration. The thirteen essays here show how the sharing of food and drink forged social, religious, and community bonds, and how ceremonial feasts as well as domestic daily meals strengthened ties and solidified ethnoreligious identity through the sharing of food customs. The very act of eating and the pleasure derived from it are metaphorically linked to two other sublime activities of the human experience: sexuality and the search for the divine. This interdisciplinary study of food in medieval and early modern communities connects threads of history conventionally examined separately or in isolation. The intersection of foodstuffs with politics, religion, economics, and culture enhances our understanding of historical developments and cultural continuities through the centuries, giving insight that today, as much as in the past, we are what we eat and what we eat is never devoid of meaning.--